2017
DOI: 10.1136/bmjgh-2016-000199
|View full text |Cite
|
Sign up to set email alerts
|

‘We identify, discuss, act and promise to prevent similar deaths’: a qualitative study of Ethiopia's Maternal Death Surveillance and Response system

Abstract: IntroductionEthiopia introduced national Maternal Death Surveillance and Response (MDSR) in 2013 and is among the first sub-Saharan African countries to capture data on facility-based and community-based maternal deaths. We interviewed frontline MDSR implementers about their experiences of the first 2 years of MDSR, including perceptions of its introduction and outcomes for health services.MethodsWe conducted a qualitative case study in 4 zones in the largest regions, interviewing 69 key informants from region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(99 citation statements)
references
References 14 publications
2
96
1
Order By: Relevance
“…Furthermore, the number of facilities whose reports were captured at national level was less than half of the number of facilities reporting to the next level. Other studies revealed that poor data flow from the facility to the central level was a challenge in both MDR and MDSR systems, and stemmed from a lack of knowledge and confusion among facility staff on the reporting process, high staff turnover and fear of legal repercussions [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the number of facilities whose reports were captured at national level was less than half of the number of facilities reporting to the next level. Other studies revealed that poor data flow from the facility to the central level was a challenge in both MDR and MDSR systems, and stemmed from a lack of knowledge and confusion among facility staff on the reporting process, high staff turnover and fear of legal repercussions [6,7,24].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple factors can affect the implementation of MDSR. Lack of awareness of the purpose and principles of MDSR among stakeholders, the existence of a blame culture, insufficient number of trained staff to implement MDSR, the unavailability of guidelines and tools, lack of commitment and financial resources all contribute to the implementation of MDSR [4][5][6][7][8][9][10][11][12][13]. These barriers may prevent compliance with national and global targets for MDSR and delay the establishment of functioning MDSR committees at all health facilities [14].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have emphasized the necessity of following maternal mortality surveillance system to reduce maternal deaths. According to these studies, decrease in the maternal mortality ratio during the recent years, compared to 1990s, has been related to the use of this system [12][13][14][15][16]. Moreover, examining the viewpoint of health workers about the maternal mortality system, other studies have had a positive attitude towards this system, and considered its exibility, acceptability and sensitivity to be valuable [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…However immediate newborn interventions and the coverage and quality of postnatal care checks lagged behind Over a decade ago the government committed to increase demand for and availability of health services everywhere and, through a comprehensive mix of multi-sectoral strategies, made remarkable progress to this end [ 15 ]. A large number of external partners played a role in supporting the government, testing for example quality improvement initiatives [ 16 ], improving access to emergency transport [ 17 ] strengthening community linkages [ 18 ], and institutionalising maternal death surveillance and response systems [ 19 ]. Current government priorities, as described in the Health Sector Transformation Plan, clearly define targets to improve the quality, not only the quantity, of health care provided.…”
Section: Discussionmentioning
confidence: 99%